Respiratory rhythm of brainstem-spinal cord preparations: Effects of maturation, age, mass and oxygenation - Fong, Angelina Y.; Corcoran, Andrea E.; Zimmer, M. Beth; Andrade, Denis V. [UNESP]; Milsom, William K. (Elsevier B.V., 2008)
We examined the effect of age, mass and the presence of the pons on the longevity (length of time spontaneous respiratory-related activity is produced) of brainstem-spinal cord preparations of neonatal rodents (rats and hamsters) and the level of oxygenation in the medulla respiratory network in these preparations. We found the longevity of the preparations from both species decreased with increasing postnatal age. Physical removal of the Pons increased respiratory frequency and the longevity of the preparation. However, tissue oxygenation at the level of the medullary respiratory network was not affected by removal of the Pons or increasing postnatal age (up to postnatal day 4). Taken together, these data suggest that the effect of removing the Pons on respiratory frequency and the longevity of brainstem-spinal cord preparations with increasing postnatal age are primarily due to postnatal development and appear to be unrelated to mass or changes in levels of tissue oxygenation. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Respiratory rhythmogenesis; Pons; Postnatal development; Rat; Hamster